GAYA KEPEMIMPINAN BIROKRATIK VS MANAJERIAL DALAM ORGANISASI PEMERINTAHAN DAERAH - A l w i1, A l w i1 (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2006)
The implementation of local autonomy policy influences the leadership model of local bureaucrats. The model of bureaucratic leadership, previously oriented more to the bureaucratic rules, changes to the managerial leadership leading to more efficient use of the organizational resources, including the human resources. The objective of local autonomy policy is to materialize, that is to accelerate the local development and public service delivery, good leadership as a precondition should be fulfilled. First, a leader should have a strong commitment. In addition, his orientation should be more on managerial skills rather than bureaucratic structure, as to focus on the achievement of development results. The practice of the effective managerial leadership model poses some key elements as guidance for the local autonomy bureaucrats. Such key elements include the objectives to be achieved, the necessary preventive actions to deal with crisis situation, the critical leadership actions to take into consideration, the expected results of leadership intervention, the follow-up steps to be taken, and the inclusion of other impending resources.